Steganography Using TCP / IP's Sequence Number - Kadhim, Jamal M; Abed, Abeer E (Al-Nahrain Journal of Science, 2017)
The exchanging process inside LAN or through the Internet may be exposed to be stolen, altered or damaged by a baleful person who was represented as real threats to transport process and also to information especially if this information was sensitive, important and must be accessed by only authorized person. Therefore this data must be secured against such threats. Steganography is classified as the art of hiding information in a suitable carrier like image, text, audio and video. It can also be applied to network protocols whether to header or payload of the packet. In this paper, steganography was implemented on the header of IP packet protocol and/or TCP segment protocol by exploiting the sequence number field of this header for hiding information inside it. In addition, four characters would be sent in every connection. So to increase the amount of information which could be sent, the number of connections must be increased.